Molecular and immunohistochemical diagnosis of Francisella noatunensis subsp. orientalis from formalin-fixed, paraffin-embedded tissues - Morales, Juan Alberto (2012)
Members of the genus Francisella (viz., F. noatunensis subsp. orientalis [Fno] and F. noatunensis subsp. noatunensis) have been described as causative agents of chronic granulomatous and pyogranulomatous lesions in wild and cultured fish species. In the present study, 68 archived formalin-fixed, paraffin-embedded (FFPE) tissues from several fish species, collected at different geographical locations from 2000 to 2011, were analyzed using a real-time polymerase chain reaction assay for the detection of the Fno intracellular growth loci C (iglC) gene and by immunohistochemistry for the demonstration of Fno antigens. The results revealed a high correlation between these 2 diagnostic techniques validating their use for the diagnosis of Fno infection in archived FFPE tissues and confirming the presence of Fno in fish species from the Cari y years of the present century.